Detection and forecasting of housing price bubbles in Indonesia, Malaysia, and Singapore - Suryati, Suryati; Rizqiana, Zulfanita Dien (Indonesian Journal of Islamic Economics Research, 2023)
Houses are commodities to fulfill basic human needs, so the demand tends to continually increase. The research aims to assess the potential for a housing price bubble and to forecast house prices in the future. The data used in this study are secondary data from three countries, Indonesia, Malaysia, and Singapore. The method used to detect a housing bubble involves comparing the data of the House Price Index with the Consumer Price Index. The observations show that the trend in house prices in Malaysia and Singapore continues to increase each year. Indonesia exhibits a fluctuating trend in house prices. The highest value of Malaysia's housing bubble ratio is 1.94 in the 2nd quarter of 2020. Based on the ARIMA modeling results, the forecasting of the House Price Index in Indonesia, Malaysia, and Singapore shows a positive trend.